Uncertainty and Information:: Foundations of Generalized Information Theory (a book review) - Vejnarová, Jiřina (Algorithmic Operations Research, 2008)
We present a review of the book by George J. Klir, Uncertainty and Information: Foundations of Generalized Information Theory, Wiley, Hoboken, New Jersey 2006, ISBN: 0-471-74867-6, 520 pp